Analisis Faktor yang Mempengaruhi Eksistensi Ritel Tradisional di Kecamatan Sumbawa Menggunakan Structural Equation Modeling - Ryan Suarantalla; Yandri Sudodo; Koko Hermanto (Performa: Media Ilmiah Teknik Industri, 2020)
Currently, in the sub-district of Sumbawa, West Nusa Tenggara province, there are many modern retail shops that have become competitors to the existence of traditional retailers that have existed before. Therefore, the aim of this research is to analyze the factors that influence the existence of traditional retailers with the existence of modern retailers in Sumbawa sub-district. This study uses a quantitative approach to statistical analysis using path analysis. The data used in this study is primary data, which is obtained through distributing questionnaires. It is known that the total population of the Sumbawa sub - district based on population data in 2019 is 61,518 people, so using the Slovin formula the number of samples for this study is at least 100 people (with an error rate of 10%). From the analysis using SEM and LISREL software obtained a mathematical model for the existence of traditional retails: existence = 0.59 decisions + 0.5 products - 0.078 price - 0.085 place + 0.49 with a value of R2 = 0.51 means the existence of traditional retail in the sub-district Sumbawa is influenced by decision, product, Price, and place varies by 51%, the remaining 49% is influenced by other variables. Meanwhile, from the results of the hypothesis analysis, it is found that the purchasing decisions of Sumbawa sub-district residents at traditional retail are influenced by price and place, while their existence is influenced by product variables and purchasing decisions. The factors that have a direct influence on the existence of traditional retail in the Sumbawa sub - district are product factors and buyer decision factors, while the factors that have an indirect effect are product factors through buyer's decision factors.